The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5897/ajb2016.15706
|View full text |Cite
|
Sign up to set email alerts
|

Growth promotion mediated by endophytic fungi in cloned seedlings of Eucalyptus grandis x Eucalyptus urophylla hybrids

Abstract: Eucalyptus cultivation has expanded considerably in Brazilian systems, leading to the current search for technologies to optimize growing conditions and the production of seedlings in nurseries. Based on the understanding that the development of tree species such as Eucalyptus sp. can be influenced by endophytic fungi that act directly as plant growth-promoting species, cloned seedlings of Eucalyptus grandis x Eucalyptus urophylla hybrids grown from minicuttings we stimulated with three species of endophytic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…Contreras-Cornejo et al (2011) reported the synthesis of the phytohormones related to auxin (indole-3acetic acid, indole-3-acetaldehyde and indole-3-ethanol) by fungal species Trichodermavirens while working with Arabidopsis thaliana. Production of growthpromoting factors was also reported from three endophytic fungal strains of the genus Trichoderma sp, Fusarium sp, and Papulasporasp by Vitorino et al (2016) while working with hybrids of Eucalyptus grandis and Eucalyptus urophylla. The fungal strains showed a direct positive influence on stem length, stem diameter, and fresh and dry biomass.…”
Section: Influence Of Endophytic Fungal Isolates On Tomato Productivi...mentioning
confidence: 93%
“…Contreras-Cornejo et al (2011) reported the synthesis of the phytohormones related to auxin (indole-3acetic acid, indole-3-acetaldehyde and indole-3-ethanol) by fungal species Trichodermavirens while working with Arabidopsis thaliana. Production of growthpromoting factors was also reported from three endophytic fungal strains of the genus Trichoderma sp, Fusarium sp, and Papulasporasp by Vitorino et al (2016) while working with hybrids of Eucalyptus grandis and Eucalyptus urophylla. The fungal strains showed a direct positive influence on stem length, stem diameter, and fresh and dry biomass.…”
Section: Influence Of Endophytic Fungal Isolates On Tomato Productivi...mentioning
confidence: 93%